Comparative Pharmacokinetics of three major bioactive components in rats after oral administration of Typhae Pollen-Trogopterus Feces drug pair before and after compatibility. Issue 1 (December 2016) - Zeng, Huiting; Xue, Ping; Su, Shulan; Huang, Xiaochen; Shang, Erxin; Guo, Jianming; Qian, Dawei; Tang, Yuping; Duan, Jin-ao
Abstract Background Typhae Pollen (TP) and Trogopterus Feces (TF) are well-known traditional medicine in china which widely used for thousands of years as drug pair called Shixiao San for treatment of blood stasis syndrome, specially shown great efficacy in gynecological disease. Typhaneoside, vanillic acid andp -coumaric acid are the main bioactive components of Typhae Pollen. This study was carried out for comparing the pharmacokinetic profile of these three major bioactive components in rats after oral administration of Typhae Pollen-Trogopterus Feces (TP-TF) drug pair before and after compatibility. Methods A sensitive and rapid UPLC-TQ/MS method has been developed for simultaneous quantification of the three main bioactive compounds in blood at different time points after oral administration of Typhae Pollen (TP) and the combination with Trogopterus Feces (TF). Results There were significant differences of Cmax, Tmax, T1/2 and AUC0 t for three bioactive compounds among the groups, for typhaneoside with the most highest plasma concentration of 370.86 ± 315.71 ng/mL and more longer Tmax in TP-TF co-decoction group (CM ); for vanillic acid, TP-TF co-decoction group (CM ) had a good absorption with Cmax (3870.99 ± 2527.99 ng/mL) and Tmax (1.47 ± 3.20 h); forp -coumaric acid, it had similar pharmacokinetic characteristics with vanillic acid. Conclusions The three bioactive components in Typhae Pollen (TP) were simultaneously determined by UPLC-TQ/MS and had a good absorption in rat plasma after the combination with Trogopterus Feces (TF).